2022
DOI: 10.1093/wber/lhac003
|View full text |Cite
|
Sign up to set email alerts
|

Jobs and Productivity Growth in Global Value Chains: New Evidence for Twenty-five Low- and Middle-Income Countries

Abstract: Using newly developed data, the evolution of job and productivity growth in global value chains (GVCs) is analyzed for 25 low- and middle-income countries. GVC jobs are found to be more productive than non-GVC jobs. Their share in the total labor force is small, in particular for low-income countries. Growth in GVC jobs varies widely across countries in the period 2000–2014. Part of this can be accounted for by differences in the type of consumer market served. A bigger part is accounted for by the speed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Some scholars believe that GVC participation widens the income gap [11]. Pahl et al indicate that the productivity of firms participating in GVC production is higher than that of non-participating firms, and, therefore, workers' wages are higher in firms participating in GVC production [12]. Meanwhile, Han et al argue that regions more affected by globalization have experienced greater changes in wage inequality than regions less affected by globalization [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars believe that GVC participation widens the income gap [11]. Pahl et al indicate that the productivity of firms participating in GVC production is higher than that of non-participating firms, and, therefore, workers' wages are higher in firms participating in GVC production [12]. Meanwhile, Han et al argue that regions more affected by globalization have experienced greater changes in wage inequality than regions less affected by globalization [13].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of participation in GVCs by developing countries have been well emphasized in the literature (e.g., Ignatenko et al, 2019;World Bank, 2020). For example, GVC participation positively affects labour productivity in low-income countries (e.g., [12]); fosters economic upgrading, including through greater developing countries productivity growth in the formal manufacturing sector (e.g., [13,14]); promotes social upgrading (e.g., [15]); contributes to lower within-country income inequality (e.g., [16,17]); promotes economic growth (e.g., [9,18]); reduces poverty (e.g., [18][19][20]); and can be beneficial for the acceptability, developability, and sustainability of the energy system (e.g., [21]).…”
Section: Introductionmentioning
confidence: 99%
“…Pahl et al, (2022), looked at jobs and productivity growth in GVCs and found GVC jobs to be more productive than non GVC jobs. Further, the study established that GVC jobs have a smaller share in the total Labour force, especially for low income countries and that expansions in GVCs is correlate with labor proactivity in a positively.…”
mentioning
confidence: 99%